Periodontal healing after application of enamel matrix derivative in surgical supra/infrabony periodontal defects in rats with streptozotocin‐induced diabetes. (24th April 2013) - Shirakata, Y.; Eliezer, M.; Nemcovsky, C. E.; Weinreb, M.; Dard, M.; Sculean, A.; Bosshardt, D. D.; Moses, O.
<x xml:space="preserve">Abstract</x> Background and Objective Epidemiologic and clinical studies have indicated that diabetes is a risk factor for periodontal disease progression and healing. The aim of the present study was to evaluate short‐term healing after enamel matrix derivative (EMD) application in combined supra/infrabony periodontal defects in diabetic rats. Material and Methods Thirty male Wistar rats were initially divided into two groups, one with streptozotocin‐induced diabetes and another one with healthy (non‐diabetic) animals. Bony defects were surgically created on the mesial root of the first maxillary molars. After root surface planing and EDTA conditioning, EMD was applied to the roots at one side of the maxillae, while those on the contralateral sides were left untreated. Animals were killed 3 wk after surgery, and block sections were prepared for histologic and histomorphometric analysis. Results There was statistically significant more gingival recession in diabetic animals than in non‐diabetic animals. The length of the junctional epithelium was significantly shorter in the EMD‐treated sites in both diabetic and normoglycemic rats. Sulcus depth and length of supracrestal soft connective tissue showed no statistically significant differences between groups. In all animals, new bone formation was observed. Although new bone occurred more frequently in healthy animals, the extent of new bone was not significantly different between groups. In none of the teeth, a layer of new cementum was detectable. EMD had no influence on bone or cementum regeneration. Adverse reactions such as excessive inflammation due to bacterial root colonization, ankylosis and bone fractures were exclusively observed in diabetic animals, irrespective of EMD treatment. Conclusion Within the limits of the present study, it can be concluded that periodontal healing was impaired in streptozotocin‐induced diabetic rats. EMD had no beneficial effects on new bone and cementum formation during short‐term healing in this defect model and could not ameliorate the adverse effects in the systemically compromised animals.